Contrecoup Head Injury - Banga, Manpreet Singh; BV, Sandeep; Roy, Kaushik; Saha, Suniti Kumar; Dixit, Sourabh; Ghosh, Partha (Indian Journal of Neurosurgery, 2017)
Contrecoup injuries comprise a group of focal brain injuries that occur at areas distant from the point of impact. It has been hypothesized that patients with contrecoup injuries would have a worse outcome because of the diffuse nature of injury. At Nilratan Sircar Medical College, Kolkata, 74 patients presenting with contrecoup injuries over a period of 1 year were prospectively analyzed. Site of primary impact was determined by clinical and CT scan criteria. The age, modes of injury, Glasgow coma scale (GCS), site of injury, pattern of injury, and mortality were analyzed. Delayed presentation of contrecoup injury in patients who deteriorated over time was also noted in imaging. The presence of contrecoup injury implies that the traumatic forces have dissipated into the brain, and from the biomechanisms explained, the brain is likely to have suffered greater damage than the case in coup injury alone. The present study shows that the presence of contrecoup contusions is associated with a poor prognosis across all GCS and age categories.
Keywords: contrecoup; coup; Glasgow coma scale